Association Between Feeling Threatened, Behaviour and Symptoms of Anxiety and Depression: Two and a Half Years After the Terrorist Attacks in Belgium - Van Overmeire, Roel; Six, Stefaan; Deschepper, Reginald; Vandekerckhove, Marie; Bilsen, Johan (Community mental health journal, 2022)
Feeling threatened by terrorism can be associated with mental health problems and behavioural changes. However, few studies look at the association in the long-term. Using a survey, the population in Brussels, Belgium was studied using a representative database delivered by the national post service. The Patient Health Questionnaire-4 (PHQ-4) assessed mental health, and self-made questions avoidance behaviour. 170 people answered: 60% women and 50% higher educated, 28.2% between 56 and 65 years and 62.4% had a partner. 43.5% felt threatened by the terrorist attacks and 45.9% experienced no mental health problems. Both terrorist threat (p < 0.001) and avoidance behaviour (p < 0.001) significantly predicted PHQ-4 scores, while controlling for gender, age, social support, education level, and traumatic events. There is a relation between terrorist threat and anxiety/depressive symptoms 2.5 years after the last study on terrorist threat in Brussels, but it has weakened. Avoidance behaviour seems to be more present than threat.